2018
DOI: 10.2147/idr.s167271
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance pattern and molecular characterization of extended-spectrum &beta;-lactamase producing enteroaggregative <em>Escherichia coli</em> isolates in children from southwest Iran

Abstract: IntroductionEnteroaggregative Escherichia coli (EAEC) has been implicated as an emerging cause of traveler’s diarrhea, persistent diarrhea among children, and immunocompromised patients. The present study aimed to investigate the prevalence of antibiotic resistance, extendedspectrum β-lactamase (ESBL) production, and virulence factors of EAEC isolates obtained from Iranian children suffered from diarrhea.Materials and methodsIn this cross-sectional study, from March 2015 to February 2016, 32 EAEC isolates were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 33 publications
(51 reference statements)
5
13
1
Order By: Relevance
“…From the 29 pathogenic isolates, 11 were found to be ESBL positive and surprisingly, 10 of them were of EAEC pathotype. In recent studies of Iran and China, a high prevalence of ESBL in EAEC was also reported (86,87). The alarming rate of ESBLproducing EAEC isolates recommends strict infection control policies to prevent additional spreading of the virulent and resistant EAEC strains.…”
Section: Discussionmentioning
confidence: 99%
“…From the 29 pathogenic isolates, 11 were found to be ESBL positive and surprisingly, 10 of them were of EAEC pathotype. In recent studies of Iran and China, a high prevalence of ESBL in EAEC was also reported (86,87). The alarming rate of ESBLproducing EAEC isolates recommends strict infection control policies to prevent additional spreading of the virulent and resistant EAEC strains.…”
Section: Discussionmentioning
confidence: 99%
“…(Salimian Rizi et al, 2015; Bialvaei et al, 2016; Aminshahidi et al, 2017). The high incidence of cephalosporins resistance in pathogenic bacteria in this country may be attributed in part to their inappropriate and high use in clinical settings (Amin et al, 2018); this is in addition to their extensive utilization in the Iranian community via self-medication (SM) (Zamanlou et al, 2018). Other ESBL producers that have been detected in clinical settings in Iran include CTX-M-15/TEM-169, SHV-12 producing Enterobacter cloacae (Peymani et al, 2014).…”
Section: Distribution Of Multi-drug Resistant Organisms In Humansmentioning
confidence: 99%
“…The bacterial colonies were identified using standard biochemical tests including coagulase, catalase, triple sugar iron agar, Simmon̍ s citrate, urease, indole production, Methyl red/ Voges-Proskauer, and oxidase. 9 When the same bacterium was isolated from three samples of one patient, only one isolate was considered for further investigation.…”
Section: Microbial Identificationmentioning
confidence: 99%